EVALUATION OF STRESS AND COPING STRATEGIES ADOPTED BY NURSING STUDENTS - CHUDARY , M; PARVEEN , T; NAZAR , K (Biological and Clinical Sciences Research Journal, 2023)
The prospective study was conducted in Nishtar Medical Hospital from November 2022 to January 2023 to evaluate stress levels and coping strategies adopted by government hospital nursing students. The study was conducted with a total of 54 participants. Three tools were used to gather data, including a questionnaire, Perceived Stress Scale (PSS-10) and Adolescent Coping Orientation for Problem Experiences (ACOPE). Results showed that according to PSS, 21 %(11) students reported mild stress, 69% (38) reported moderate levels of stress, and 10% (5) reported a severe level of stress. The most commonly used strategies were practicing breathing or muscle relaxation technique (42%), followed by having a hobby (40%) and meditation (39%). Moreover, it was also observed that some students (31%) pray to manage their stress. Most nursing students suffer moderate stress due to workload, patient care, peer pressure, and academic stressors. Faculty members should know students' stress levels and concentrate on providing a program to help them manage it.